European Country Clusters of Transition to Adulthood - Isoniemi, Henna (fi=Turun yliopisto|en=University of Turku|, 2017)
The  purpose  of  this  study  is  to  perform  a  cross‐country  comparison  of  the  transition‐to‐adulthood  patterns  and  timings  of  young  adults  and  analyse  the  relationship  between  these  patterns  and  timings.  Another  aim  is  to  gain  new  insight  on  late  transitions  and  to  clarify  the  concept  of  incomplete  transitions  affecting young Europeans’ life courses. Based on these distinct points of view, the  main  goal  is  to  construct  transition‐to‐adulthood  patterns  describing  the  current  situation  in  20  European  countries.  Transition  to  adulthood  has  been  widely  discussed as a general subject, but there is a lack of systematic and comparative  empirical research covering the combination of events constituting the transition‐ to‐adulthood process. This study contributes to filling this gap. This is done by using  two main data sets: the European Social Survey (ESS) data set (2006/2007) and the  European  Union  Statistics  on  Income  and  Living  Conditions  (EU‐SILC)  data  set  (2012). Cross‐country statistical data have also been obtained from Eurostat, the  OECD Family Database and the UNECE Statistical Database.  In general, the transition‐to‐adulthood process of all young adults involves leaving  the  parental  home,  entering  the  labour  market,  forming  a  partnership,  and  childbearing  and  childrearing.  However,  adult  status  can  be  achieved  through  a  number of different routes, the duration of the voyage varies widely and transition  paths  are  increasingly  being  replaced  by  de‐standardised  and  prolonged  ones  which  not  only  take  longer  to  walk  through  but  are  also  diversified  and  individualised. Late and incomplete transitions have also come to stay, and it may  be  time  to  question  the  role  of  demographic  adulthood  markers.  It  has  already  been  suggested  that  the  most  important  markers  of  adulthood  are  those  that  represent becoming independent from others and learning to stand alone as a self‐ sufficient individual.    The results of this thesis show that there is variation between European countries  in  terms  of  young  adults’  transition  processes,  although  similarities  can  also  be  observed. These differences between countries and between the clusters that have  been created are not a surprise: despite the closeness and commonalities of the 20  European  countries  included  in  this  study,  their  institutional  arrangements,  economies and cultures are diverse. There are also clear differences between the  transition‐to‐adulthood  clusters  formed  in  this  study  and  the  groupings  used  in  earlier studies. Country groupings used in previous studies are normally based on a  welfare‐regime‐type model that clusters groups of countries according to a specific  rationale. Ultimately, most of the results of this study indicate that this rationale  does  not  provide  the  most  suitable  approach  for  building  different  transition‐to‐ adulthood clusters or models. The results unambiguously show that the indicators  the transition‐to‐adulthood classification is based on have an enormous impact on transition‐to‐adulthood groupings. The indicators may even prove to be decisive.  Nevertheless, the results of this study clearly indicate that it is difficult to produce  credible  and  comprehensive  generalizations  about  transition‐to‐adulthood  patterns. The only exception is provided by the Nordic countries (with some minor  exceptions): in spite of the approach used, young adults in these countries seem to  follow  quite  similar  transition  patterns.  Southern  European  Portugal  and  Eastern  European Bulgaria also seem to have many similarities throughout the analyses of  this study.    Since  the  differences  between  regions,  and  even  between  countries,  are  rather  substantial, Europeans will almost certainly continue to follow divergent patterns in  their  transition‐to‐adulthood  processes.  Currently,  young  adults’  transition  processes are more challenging than before as they are being made in a social and  economic  context  that  is  extremely  insecure  and  unstable.  The  effects  of  the  economic crisis, which began in 2008, have hit young Europeans particularly hard.  This means that the management of transition‐to‐adulthood processes needs to be  improved. At the European level, there are already many good practices to follow.  European heterogeneity, however, makes it very challenging to propose common  guidelines that could be applied in all countries.

Tässä  tutkimuksessa  tarkastellaan  eurooppalaisten  nuorten  aikuisten  siirtymää  aikuisuuteen. Aihetta lähestytään monesta eri näkökulmasta: työn empiriaosuuden  alussa  pohditaan,  mitkä  aikuistumiseen  liitettävät  demografiset  siirtymät  kuvastavat aikuisuutta, mitkä eivät. Analyysiä jatketaan tutkimalla, milloin nämä eri  siirtymät  ajallisesti  tapahtuvat.  Näiden  tarkasteluiden  jälkeen  kartoitetaan,  mikä  yhteys  siirtymien  tärkeänä  tai  tarpeettomana  pitämisellä  on  siihen,  milloin  siirtymät konkreettisesti tapahtuvat. Monien aiempien tutkimusten tapaan tässäkin  tutkimuksessa osoitetaan, että useat siirtymät tapahtuvat verrattain myöhään. Siksi  empiriaosuuden  lopuksi  tarkastelu  keskittyy  myöhäisiin  sekä  keskeneräisiin  ja  vaillinaisiin  siirtymiin.  Näitä  eri  näkökulmia  käyttäen  rakennetaan  erilaisia  aikuisuuteen  siirtymisen  maaryhmiä.  Tutkimuksen  empiirisinä  aineistoina  käytetään European Social Survey (ESS) ‐aineistoa vuosilta 2006 / 2007, European  Union Statistics on Income and Living Conditions (EU‐SILC) ‐aineistoa vuodelta 2012  sekä  tilastoaineistoja  Eurostatilta,  OECD:ltä  ja  UNECE:ltä  eri  vuosilta.  Tutkimus  käsittää 20 Euroopan maata.  Perinteisesti  tarkasteltuna  aikuistumiseen  liitettäviä  siirtymiä  ovat  muutto  pois  lapsuudenkodista,  siirtyminen  opinnoista  työelämään,  parisuhteen  solmiminen  ja  lapsen  hankkiminen.  Nuorten  elämänkulku  on  kuitenkin  poikennut  viime  vuosina  aikuistumisen  perinteisestä  mallista.  Enää  erilliset  siirtymät  eivät  välttämättä  tapahdu  tietyn  ikäisinä,  tietyssä  odotetussa,  normien  mukaisessa  järjestyksessä,  vaan  aiempaan  verrattuna  myöhempään  tai  ne  jäävät  kokonaan  toteutumatta.  Siirtymä  aikuisuuteen  on  nykyään  monelle  eurooppalaiselle  nuorelle  asteittain  etenevä,  yksilöllinen  prosessi.  Muutosten  seurauksena  on  myös  alettu  pohtia,  kuvastavatko  perinteiset  siirtymät  enää  nykytilannetta.  Aikuisuuteen  siirtymisen  keskeisinä  merkkeinä  onkin  esitetty  olevan  ennemmin  esimerkiksi  kyky  huolehtia  itsestään tai kyky tehdä itsenäisiä päätöksiä.    Tutkimuksen  tulokset  osoittavat,  että  siirtymä  aikuisuuteen  eroaa  merkittävästi  Euroopan  maiden  välillä,  mutta  tietyissä  maissa  näkemykset  ja  toimintatavat  muistuttavat  toisiaan.  Näkökulmasta  riippumatta  yhteneväisiä  piirteitä  on  havaittavissa  vain  Pohjoismaiden  välillä  (Suomi,  Ruotsi,  Norja,  ja  Tanska  osassa  analyyseistä).  Tämän  lisäksi  portugalilaisten  ja  bulgarialaisten  nuorten  aikuisten  ajatuksissa  ja  käyttäytymisessä  on  löydettävissä  yhteneväisyyttä.  Kuitenkaan  ylipäänsä  se,  että  maiden  välillä  ilmenee  eroja  ja  se,  että  analyysien  perusteella  muodostetut  maaryhmittymät  eroavat  toisistaan,  ei  ole  yllätys.  Eurooppa  on  edelleen  hyvin  heterogeeninen,  eivätkä  kansalliset  erot  ole  kadonneet  globalisaation  myötä.  Nuoren  aikuisen  aikuistumisen  mahdollisuuksia  ohjaavat  kussakin maassa esimerkiksi institutionaaliset järjestelmät, hyvinvointivaltio, perhe,  työmarkkinat ja koulutusjärjestelmä sekä kulttuuriset perinteet.   Tämän tutkimuksen tulokset eroavat selkeästi myös aiemmista tutkimustuloksista.  Vertaileva tutkimus aihepiiristä on perinteisesti hyödyntänyt maaryhmittelyissään  klassista  hyvinvointiregiimiluokittelua.  Tämän  tutkimuksen  tulokset  osoittavat  yksiselitteisesti,  että  kyseinen  lähestymistapa  ei  ole  käyttökelpoisin,  kun  tehdään  vertailevaa aikuisuuteen siirtymisen tutkimusta. Käytetty näkökulma ja käytettävät  indikaattorit määrittävät keskeisesti sen, miten maat ryhmittyvät toisiinsa.   Tutkimuksessa  havaittavat  erot  eri  maiden  välillä  antavat  aiheen  epäillä,  että  eurooppalaisten  nuorten  siirtymät  aikuisuuteen  olisivat  jatkossakaan  samanlaisia  eri  maissa.  Aikuisuuden  saavuttamisen  haasteet  ovat  tällä  hetkellä  erityisen  näkyvät, sillä vuonna 2008 alkanut taloudellinen taantuma iski erityisesti nuoriin –  tietyissä  maissa  vieläpä  erityisen  voimakkaasti.  Euroopan  tasolla  on  kuitenkin  monia  hyviä  käytäntöjä  nuorten  aikuisten  aikuistumisen  tueksi,  mutta  kuten  todettu,  yhteisten  suuntaviivojen  hahmottaminen  tulee  olemaan  jatkossakin  haastavaa.